Racial residential segregation and risky sexual behavior among non-Hispanic blacks, 2006–2010. (September 2015) - Lutfi, Khaleeq; Trepka, Mary Jo; Fennie, Kristopher P.; Ibanez, Gladys; Gladwin, Hugh
Abstract: Sexually transmitted infections (STIs) including human immunodeficiency virus (HIV) have disproportionately affected the non-Hispanic black population in the United States. A person's community can affect his or her STI risk by the community's underlying prevalence of STIs, sexual networks, and social influences on individual behaviors. Racial residential segregation—the separation of racial groups in a residential context across physical environments—is a community factor that has been associated with negative health outcomes. The objective of this study was to examine if non-Hispanic blacks living in highly segregated areas were more likely to have risky sexual behavior. Demographic and sexual risk behavior data from non-Hispanic blacks aged 15–44 years participating in the National Survey of Family Growth were linked to Core-Based Statistical Area segregation data from the U.S. Census Bureau. Five dimensions measured racial residential segregation, each covering a different concept of spatial variation. Multilevel logistic regressions were performed to test the effect of each dimension on sexual risk behavior controlling for demographics and community poverty. Of the 3643 participants, 588 (14.5%) reported risky sexual behavior as defined as two or more partners in the last 12 months and no consistent condom use. Multilevel analysis results show that racial residential segregation was associated with risky sexual behavior with the association being stronger for the centralization [aOR (95% CI)][2.07 (2.05–2.08)] and concentration [2.05 (2.03–2.07)] dimensions. This suggests risky sexual behavior is more strongly associated with neighborhoods with high concentrations of non-Hispanic blacks and an accumulation of non-Hispanic blacks in an urban core. Findings suggest racial residential segregation is associated with risky sexual behavior in non-Hispanic blacks 15–44 years of age with magnitudes varying by dimension. Incorporating additional contextual factors may lead to the development of interventions that promote healthier behaviors and lower rates of HIV and other STIs. Highlights: We examine the association of residential segregation and risky sexual behavior. Multilevel regressions used to explore individual and community-level factors. Segregation measured by indices for each of five different dimensions. Centralization and concentration indices associated with risky sexual behavior.